The evolving nexus of women’s empowerment and child nutrition in India - Singh, Bharti; Singh, Shri K. (Frontiers in Public Health, 2025)
BackgroundIndia has one of the highest burdens of child undernutrition, globally. Undernutrition is a persistent challenge despite the country’s economic growth. Empowering women is essential in addressing child undernutrition since empowered mothers are more inclined to obtain healthcare, enhance dietary diversity, and make informed choices that benefit their children’s health outcomes.ObjectiveThe study aims to investigate the relationship between women’s empowerment and child undernutrition in India from 2006 to 2021.MethodsThis study is based on three recent rounds of the National Family Health Survey. A composite index of women’s empowerment has been used to measure women’s empowerment. Further, binary logistic regression and decomposition analysis have been used to analyze the association and identify the key determinants that contribute to the reduction of undernutrition among children in India.ResultOur research offers significant insights into the evolving dynamics of child undernutrition in India, particularly concerning the linkages with women’s empowerment. While empowerment was statistically insignificant in NFHS-3, it became a significant driver of child undernutrition in NFHS-4 (−0.12**[−0.21, −0.03]) and NFHS-5 (−0.15***[−0.24, −0.06]). Additionally, birth order, birth weight, and mother’s BMI are critical determinants of undernourishment status among children under age five. Wealth remains a consistently significant factor across all three survey rounds. Decomposition analysis further reinforces the significance of women’s empowerment, demonstrating that it accounts for a 3.3% reduction in child undernutrition In India.ConclusionThe study underscores the critical role that empowering woman plays in combating child undernutrition, indicating the need for comprehensive strategies that prioritize women’s empowerment alongside other critical determinants to effectively tackle the persistent challenge of child undernutrition in India.